2014
DOI: 10.1089/chi.2013.0161
|View full text |Cite
|
Sign up to set email alerts
|

The Food Environment of Youth Baseball

Abstract: Background: Sports, such as youth baseball (YB), are popular outlets for increasing activity, yet there has been no investigation of food environments surrounding them. The aim of this study was to observe the types of foods available and consumed by players and spectators at YB events.Methods: This was an observational assessment, by environmental scan, of foods consumed by players and family members at a YB field in northwest North Carolina.Results: Participants included boys from six YB teams (n = 51) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…It is therefore concerning that the majority of recreation and sport facilities had unhealthy food environments regardless of the presence of voluntary nutrition guidelines. This is consistent with our previous findings in recreation facilities in Canada [1, 2, 4, 16], and with studies internationally in a variety of sports settings [40, 5559]. As identified in a recent systematic review, there is almost no knowledge of how to improve policy implementation in sports settings, with just three controlled studies meeting inclusion criteria [60].…”
Section: Discussionsupporting
confidence: 88%
“…It is therefore concerning that the majority of recreation and sport facilities had unhealthy food environments regardless of the presence of voluntary nutrition guidelines. This is consistent with our previous findings in recreation facilities in Canada [1, 2, 4, 16], and with studies internationally in a variety of sports settings [40, 5559]. As identified in a recent systematic review, there is almost no knowledge of how to improve policy implementation in sports settings, with just three controlled studies meeting inclusion criteria [60].…”
Section: Discussionsupporting
confidence: 88%
“…Children may consume a greater proportion of energy intake from carbohydrates such as granola bars, sweetened cereals, pastry, candy, pretzels, bread, and sports drinks before, during, or after organized sports and at activity-based classes/lessons (e.g., karate, dance). This may be because these foods dominate the concessions sold at these events, are often given out as postgame treats, and serve a substitute for regular meals that are disrupted due to sports games and practices ( 39 41 ). In fact, a growing body of evidence suggests that youth sports may expose children to an unhealthy food environment ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in a North Carolina youth baseball league observed 12 team snacks in six youth baseball teams. The results showed that most (72%) snacks included high‐calorie items such as French fries, candy, and cookies, and about half (53%) of the beverages consumed by players were sugar‐sweetened (Irby, Drury‐Brown, & Skelton, ; Thomas, Nelson, Harwood, & Neumark‐Sztainer, ). A qualitative study conducted among parents in two Minnesota youth basketball programs (one serving primarily African American families of low to middle socioeconomic status and another serving primarily white families of middle to high socioeconomic status) found parents to be aware of unhealthful foods and beverages consumed in the youth sport context (Thomas et al, ).…”
Section: Review Of Literaturementioning
confidence: 99%